Determinants of sertu cleansing integrity in halal logistics operations in Malaysia / Noorsiah Ahmad - Ahmad, Noorsiah (2018)
The motive for halal logistics is to assure integrity of product and maintaining the halal status throughout the supply chain from the halal certified manufactures and to the consumers.